Pengaruh Jenis Pengekstrak dan Jenis Pati Terhadap Sifat Gel Cincau yang Dibuat Dengan Ekstraksi dan Pemasakan Optimal - Bangun P. Nusantoro; Haryadi Haryadi; Supriyadi Supriyadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1998)
Black cincau (Mesona palustris) gel is made traditionally by boiling a mixture containing the alkaline extract of the herb and starch followed by cooling to room temperature. In this study, herb extraction time and boiling time of the mixed stuff were optimized based on the smallest degree of syneresis of the gel following cold storage. The alkaline solutions use were solution of qi (traditional alkali) ash and of NaOH at pH 11 and the starches were of tapioca, aren (Arenga pinata) and sago. Effects, of type of alkaline solutions and different starches on the characteristics of gel were also studied. The optimum extraction time using qi ash 4% was 70 min. When the extraction using NaOH at pH 11 was effected, it needed 60 min to get the extract which resulted the most stable gel. The optimum boiling time of the qi extract mixed with tapioca, aren, and sago starches were 60, 40, and 50 min, respectively. Boiling the NaOH extract mixed with tapioca, aren, and sago starches needed 70, 40, and 50 min, respectively, to get the best result. Extraction using qi 4% gave higher total solid of the extract and higher pH of the gel. The highest breaking strength of the gel was produced when the fornulae comprising qi solution and aren was adopted. The gels made from qi extract boiled along with aren and sago starches gave more acceptable gels than that along with tapioca starch. Extraction using the NaOH solution improved the acceptability of the gel made with tapioca starch.